EBM E-learning: Feasible and Effective for Occupational Physicians in Different Countries - Nathalie I.R. Hugenholtz; Judith K. Sluiter; Frank J.H. Van Dijk; Karen Nieuwenhuijsen (Elsevier, 2012)
Objectives: Although evidence-based medicine (EBM) is a useful method for integrating evidence into the decision-making process of occupational physicians, occupational physicians lack EBM knowledge and skills, and do not have the time to learn the EBM method. In order to enable them to educate themselves at the time and place they prefer, we designed an electronic EBM course. We studied the feasibility and utility of the course as well as its effectiveness in increasing EBM knowledge, skills, and behaviour. Methods: Occupational physicians from various countries were included in a within-subjects study. Measurements were conducted on participants' EBM knowledge, skills, behaviour, and determinants of behaviour at baseline, directly after finishing the course and 2 months later (n = 36). The feasibility and utility of the course were evaluated directly after the course (n = 42). Results: The course is applicable as an introductory course on EBM for occupational physicians in various countries. The course is effective in enhancing EBM knowledge and self-efficacy in practising EBM. No significant effect was found on EBM skills, behaviour, and determinants of behaviour. After the course, more occupational physicians use the international journals to solve a case. Conclusion: An electronic introductory EBM course is suitable for occupational physicians. Although it is an effective method for increasing EBM knowledge, it does not seem effective in improving skills and behaviour. We recommend integrating e-learning courses with blended learning, where it can be used side by side with other educational methods that are effective in changing behaviour.